TINDAK TUTUR ILOKUSI KOMISIF DAN DIREKTIF DALAM INTERAKSI JUAL BELI SUSU MURNI DI PASARBATANG BREBES - Hanung Erianata; Nurchalistiani Budiana; Prasetyo Yuli Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the importance of language use in the interaction between sellers and buyers of fresh milk in Pasarbatang Brebes. In the transaction process, the utterances used by sellers and buyers not only function to convey information but also contain certain intentions that can be studied through illocutionary speech acts. This study aimed to describe the forms and functions of commissive and directive illocutionary speech acts used in the interaction of buying and selling fresh milk in Pasarbatang Brebes. This research employed a descriptive qualitative approach. The research data consisted of spoken utterances of sellers and buyers obtained through observation, recording, and documentation. Data validity was ensured through technique triangulation and time triangulation. Data analysis was conducted by identifying, classifying, and describing the forms of speech acts based on the context of the utterances. The results of the study showed that there were various forms of commissive and directive illocutionary speech acts in the interaction of buying and selling fresh milk in Pasarbatang Brebes. Commissive speech acts included offering, promising, and convincing buyers about product quality, while directive speech acts included requesting, bargaining, suggesting, inviting, and commanding. The use of these speech acts indicates that language plays an important role in influencing, convincing, and building agreements between sellers and buyers in the transaction process.